2019
DOI: 10.3324/haematol.2018.198549
|View full text |Cite
|
Sign up to set email alerts
|

Fecal microbiota transplantation before or after allogeneic hematopoietic transplantation in patients with hematologic malignancies carrying multidrug-resistance bacteria

Abstract: Fecal microbiota transplantation is an effective treatment in recurrent Clostridium difficile infection. Promising results to eradicate multidrug-resistant bacteria have also been reported with this procedure, but there are safety concerns in immunocompromised patients. We report results in ten adult patients colonized with multidrug-resistant bacteria, undergoing fecal microbiota transplantation before (n=4) or after (n=6) allogeneic hematopoietic stem cell transplantation for hematolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(87 citation statements)
references
References 29 publications
5
80
0
2
Order By: Relevance
“…Another small retrospective case-matched study of 20 patients in France showed 80% (8/10) of patients cleared CRE or CRE/Acinetobacter colonization 14 days after FMT versus 20% (2/10) in the control group [24]. In other small studies (n = 8 to 20) with various endpoints, the effectiveness of decolonization ranged from 20% to 93% [1,[25][26][27][28][29]. One study by Davido et al suggests that based on an 87% decolonization rate of VRE at three months, FMT should be further explored to combat outbreaks within hospitals [30].…”
Section: Fecal Microbiota Transplantationmentioning
confidence: 97%
See 1 more Smart Citation
“…Another small retrospective case-matched study of 20 patients in France showed 80% (8/10) of patients cleared CRE or CRE/Acinetobacter colonization 14 days after FMT versus 20% (2/10) in the control group [24]. In other small studies (n = 8 to 20) with various endpoints, the effectiveness of decolonization ranged from 20% to 93% [1,[25][26][27][28][29]. One study by Davido et al suggests that based on an 87% decolonization rate of VRE at three months, FMT should be further explored to combat outbreaks within hospitals [30].…”
Section: Fecal Microbiota Transplantationmentioning
confidence: 97%
“…Furthermore, if any microbiome therapy is going to be used for MDRO treatment or prevention, clear guidelines for use in gram-positive versus gram-negative infections and various mechanisms of resistance are necessary, as FMT has not been particularly efficacious with MDR gram-negative bacteria so far [44,45]. Some have speculated that FMT could be less effective for ESBL decolonization, although the mechanism by which this is possible has yet to be defined [25,58]. Finally, research needs to show more than a lack of inferiority; rather, studies should be designed to measure outcomes where FMT or probiotic therapies could show an advantage beyond acute treatment (e.g., reduced readmission, fewer subsequent infections, and fewer long-term complications).…”
Section: Probiotics and Prebioticsmentioning
confidence: 99%
“…One possible reason why patients with C. difficile and co-colonized with Candida species may not respond to FMT is that C. albicans has also been shown to affect gut bacterial reconstitution or recolonization after antibiotic administration [19]. Given that FMT has become an attractive treatment strategy, not only for C. difficile infection or GI disorders but also to mitigate other treatmentrelated toxicities such as GvHD, immune checkpoint inhibitor-associated colitis, and antibiotic resistant infection, one must consider the fungal contribution to the effectiveness of this strategy [41][42][43][44].…”
Section: Fungal-bacterial Interactions To Consider In the Patient Witmentioning
confidence: 99%
“…Similar findings were reported by Battipaglia et al, who performed FMT by enema or Table 1 FMT studies in HSCT recipients for the treatment of CDI. nasogastric tube in 10 patients before (n = 4) or after (n = 6) allogeneic HSCT [75]. Overall, the bulk of data indicate that FMT is safe in HSCT recipients and its use may extend beyond the treatment of recurrent CDI.…”
Section: Fecal Microbiota Transplantation For Microbiota Restoration mentioning
confidence: 99%